Hambatan Pelaksanaan Hasil Mediasi Antara Pengembang Perumahan Di Yogyakarta Dan Konsumen: Hindrance To Implementation Of The Results Of The Mediation Between Housing Developer And Consumers - Salsabila, Shindy Nabila; Sulistyarini, Rachmi; Riskawati, Shanti (WARKAT, 2023)
This research studies the hindrance to the implementation of the result of mediation between a housing developer and consumers facilitated by the Ombudsman of the Special Region of Yogyakarta. This case has been handled by the ombudsman since early 2019, while the agreement outlined in the memorandum of understanding fails to be implemented. Article 6 paragraph (6) and Article 6 Paragraph (7) of Law Number 30 of 1999 concerning Dispute Resolution Arbitration and Alternative (UU APS) has set a provision implying that mediation is implemented within 30 days, and this provision is outlined in a written agreement which is binding and final to all parties who are required to enforce this provision with good faith. This mediation is to be registered to a local District Court. However, there are two impeding factors such as procedural and substantive matters. The procedural matters are related to the absence of the basis of the law that states that the ombudsman complies with UU APS regarding the mediation. On the other hand, substantive factors are triggered by insufficient funds owned by the developer, the dominant bargaining position possessed by a consumer, and lack of understanding of the parties involved in the dispute regarding the legal principles and limited role of mediators.